Problem-Based Learning Towards Student's Motivation: An Action Research - Jothy, Karismara Olivya Afiva; Winarno, Nanang; Hakim, Lukman; Wahyuningsih, Yuyun; Nurhaida, Popi (PILLAR OF PHYSICS EDUCATION, 2024)
Students' learning motivation is still very low, this can be seen when there are still many students who pay less attention to the teacher's explanation, lack enthusiasm when participating in learning, and prefer to chat with other students and play alone in learning. This study aims to increase students' learning motivation in science learning using Problem-Based Learning. This research is a class action research consisting of 2 cycles. The sample in this research amounted to 33 students from one of the junior high schools in Bandung City consisting of 16 male students and 17 female students.. This research instrument is a questionnaire of student learning motivation consisting of 5 indicators, namely intrinsic motivation, career motivation, self-determination, and efficacy of and value motivation with 5 questions for each indicator and a total of 25 questions. Data analysis in this study is a descriptive analysis by comparing the percentage of students' learning motivation results in cycle 1 with cycle 2. Based on the results of data analysis that has been done, the results of student learning motivation in cycle 1 are 65% and in cycle 2 to 70%. Thus, there was an increase of 5% from cycle 1 to cycle 2. So, it can be concluded that the Problem-Based Learning model can increase students' learning motivation in the material of motion and force of science class VII SMP.